Adsorption of hazardous cationic dye onto the combustion derived SrTiO3 nanoparticles: Kinetic and isotherm studies*. Issue 1 (1st March 2016) - Bhagya, N.P.; Prashanth, P.A.; Raveendra, R.S.; Sathyanarayani, S.; Ananda, S.; Nagabhushana, B.M.; Nagabhushana, H.
Abstract: In this article we report on solution combustion method to synthesize SrTiO3 nanoparticles (ST-NPs) and the removal of malachite green (MG) azo dye from the aqueous solution. The synthesized ST-NPs were calcined at 600 °C for 2 h. Powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), and Brunauer–Emmett–Teller (BET) were used to characterize the product. Adsorption experiments were performed with cationic malachite green (MG) dye. ∼98% dye was adsorbed onto the ST-NPs at pH 10 for 30 min of the contact time. The optimum adsorbent dose was found to be 0.015 g/L of the dye. To study the adsorption kinetics Langmuir Hinshelwood model was used and the first order kinetic best describes the MG adsorption onto the ST-NPs. The adsorption isotherms data of MG onto ST-NPs obtained were analyzed by Langmuir and Freundlich isotherm models and the results describe the best representation of the Langmuir isotherm model.